Vicente Sáenz: presencia y exilio mexicano - Oliva-Medina, Mario (2017)
This essay presents an intellectual biography of Vicente Sáenz, a Costa Rican based-in Mexico multi-faceted character. This paper seeks to release from forgetfulness the life and deeds of this outstanding thinker, journalist, editor, professor and politician in order to bring him back into our collective memory.